How does Logistics Outsourcing Influence Organisation Performance? - Kavčič, Klemen; Gošnik, Dušan; Beker, Ivan; Suklan, Jana (International Journal of Industrial Engineering and Management, 2015)
The purpose of this research is to provide an understanding how logistics outsourcing leads to performance improvement from an organisational policy perspective.The paper aims to focus on the contribution and on the characteristics of logistics outsourcing (basic, customised and advanced outsourcing). The research provides an empirical analysis from a survey of 295 representatives of Slovenian organisations. Our intention is to focus on the outsourcing of logistics services, when a company decide to outsource a logistic service and which criteria or characteristics of such services are important for them. We found out that basic and advanced outsourcing services are closely connected to Slovenian organisations. The findings are useful for business practice in general and formanagers, as they will better understand the influences of advanced outsourcing services as the key element of long-term supply-chain success. Article history: Received (11.04.2015); Revised (12.08.2015); Accepted (03.09.2015)